FORCE MAJEURE IN SHARIA AGREEMENTS: CRITICAL REFLECTIONS ON CUSTOMER LEGAL PROTECTION IN THE MIDST OF PUBLIC POLICY CHANGES - Arifin, Desi Siti Habibah; Mukhlas, Oyo Sunaryo (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
This article aims to critically analyse the application of force majeure in sharia contracts, particularly in the context of economic disputes resulting from public policies. By exploring the court decisions in this case, this study seeks to identify weaknesses in the sharia legal protection system and offer solutions to strengthen justice for the parties involved. The research method used is a qualitative approach with normative juridical research design and case-based analysis. This study aims to analyse in depth the application of force majeure clauses in sharia contracts, particularly in the dispute between PT Lissa Sejahtera Mandiri and Bank Nagari Syariah, by linking it to the legal protection of customers in the context of public policy changes. This case underscores the need for better synergy between sharia principles, contract implementation, and public policies that often become external obstacles. Courts are expected to not only focus on the formality of the agreement, but also consider the substance of justice in accordance with sharia principles.